IMPLEMENTASI STATISTICAL PROCESS CONTROL UNTUK PENGENDALIAN KUALITAS GARAM TRADISIONAL DI KABUPATEN PIDIE - Pamungkas, Iing; Irawan, Heri Tri; Arkanullah, Lian (Jurnal Optimalisasi, 2018)
Pidie is one of the districts that has a large coastline and is widely used for traditional salt production. Pidie Regency has a salt production business with total production reaching 449.05 tons / month, and production area has reached 28.74 hectares with 451 salt farmers. The problem faced in the traditional salt production business in Pidie District is that there is no integrated quality control in the results of traditional salt production. The purpose of this study is to apply statistical process control methods to control the quality of traditional salt in the salt business group of the Saho Adab community in Keude Ie Leubeu Village, Kembang Tanjong District, Pidie Regency. Statistical process control is a statistical analysis technique used to ensure that processes meet standards. Statistical process control techniques in this study will use three quality control tools, namely pareto diagrams, control charts, and cause effect diagrams. After controlling the quality of salt in the Saho Adab Pidie District using statistical process control techniques as seen from the control map, no salt sample data were found that went out of control limits. Whether it's for NaCl levels or salt particle size. Factors affecting the quality of salt production such as human, machine, material, method and environment factors.